Hemangiosarcoma in the radius of a dog treated by limb-sparing surgery - Macedo, Aline Schafrum [UNESP]; Alievi, Marcelo Meller; Silva, Renato Barbosa; Gouvêa, Aline Silva; Dal-Bó, Ísis dos Santos; Gomes, Danilo Carloto; Driemeier, David; Minto, Bruno Watanabe [UNESP] (My University, 2014)
Background: Hemangiosarcoma is a malignant neoplasm particularly rare as a primary bone tumor. The standard treatment for dogs with this neoplasm usually takes limb amputation. The aim of this paper is to report a primary hemangiosarcoma on the distal radius, treated by limb-sparing surgery. Case: An 11-year-old mixed breed male intact dog with body weight of 30 kg was admitted to the Veterinary Teaching Hospital of the Federal University of Rio Grande do Sul (HCV-UFRGS) with previous history of progressive lameness on the right forelimb for a few months. Physical examination was unremarkable. The orthopedic examination revealed grade 4/5 lameness, swelling of the distal radioulnar joint with severe pain at palpation. Radiographs revealed intense osteolysis of the distal radial epiphysis with no involvement of the ulna and carpal bones. Biopsy revealed bone hemangiosarcoma. Chest radiographs and abdominal ultrasound showed no abnormalities or signs of metastases. The treatment of choice was limb-sparing surgery with the use of allogeneic cortical graft from bone bank preserved in glycerol 98% at room temperature. Arthrodesis was performed with a 4.5 mm dynamic compression plate with 10 holes and eight screws. Histological analysis of the bone fragment confirmed the diagnosis. The dog recovered satisfactory limb function and within 15 days postoperatively presented grade 2/5 lameness. Radiographs at 30 and 60 days after surgery displayed no radiographic signs of bone integration at the bone-graft interface, however orthopedic examination on both occasions showed walking improvement with grade 1/5 lameness. On the 90th day postoperatively, physical examination revealed edema, sinus and pus where the plate was located and pain at palpation. Radiographs were performed and displayed graft and bone resorption. Antimicrobial therapy was initiated. One hundred and twenty days after surgery the infection had not been effectively countered and osteolysis and signs of osteomyelitis were seen on radiographs. Orthopedic examination revealed worsening on lameness (grade 4/5), swelling and severe pain at palpation of the limb's distal aspect. The right forelimb lost its function and was severely contaminated so amputation was necessary. Discussion: This particular neoplasm is unusual in bone and has been satisfactorily identified by biopsy and subsequent histopathological analysis. The radiographic aspect of the tumor was characterized by extensive area of osteolysis of the radius, usual to hemangiosarcoma at this presentation. The limb salvage surgery is a viable alternative to amputation in dogs, especially in animals with concomitant orthopedic conditions, neurological problems or when the owner does not accept the amputation. The owner chose limb salvage as first option but with the infection installed and failure of the antibiotic treatment, amputation was needed. The dog recovered satisfactory limb function soon after graft implantation and had remarkable muscle gain in about three weeks, consistent with other studies. There was also weight gain and improvement in quality of life. Bacterial infection with subsequent osteomyelitis occurred, both common complications in limb-sparing cases due to the extensive surgical approach. Antibiotic therapy was not efficient. Uncharacteristically the dog from this study was in good health and free of metastases when this paper was finalized, reaching 15 months of survival after identification of the tumor, despite other reports. Limb-sparing is a viable technique, but like any surgical procedure, is subjected to complications.
Keywords: Animal; Canine; Oncology; Orthopedics; Tumor